Enhance Mothers' Knowledge and Skills in Choking First Aid through Self-Directed Learning with Video Resources - Aprioni, Anugerah; Astari, Asti Melani; Supriati, Lilik (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2024)
Choking represents a life-threatening emergency that necessitates immediate intervention, making bystanders' knowledge and skills essential for practical first aid. Traditional training methods, such as PowerPoint presentations and printed materials, are widely employed; however, technological advancements have prompted the exploration of self-directed learning through video (SDL-V) as a potentially more effective approach. This study aims to evaluate the impact of SDL-V-based choking first aid training on mothers' knowledge and skills concerning toddler choking in Kalisongo village. Employing a quasi-experimental pretest-posttest design with a control group, 30 participants from the intervention and control groups were selected through simple random sampling. Knowledge and skills were assessed before and after training, and differences were analyzed using independent and paired sample T-tests. The N-Gain Score test was employed to determine the effect size. The results revealed no significant differences in knowledge and skills between the groups before training (P > 0.05). Nonetheless, significant improvements were noted within each group following the training (P < 0.05). The intervention group exhibited significantly higher levels of knowledge and skills compared to the control group after training (P < 0.05), demonstrating a high N-Gain Score (>0.70). In conclusion, SDL-V-based choking first aid training significantly enhances mothers' knowledge and skills in Kalisongo village. Healthcare professionals should consider the integration of SDL-V into public education and training programs.